Management and Prevention of Surgical Site Infections in Spine Surgery in a Resource Poor Setting: The Irrua Protocol - Eghosa Morgan; John Enekele Onuminya; Edward Poluyi; Itaman Usifoh (Iranian Journal of Neurosurgery, 2022)
Background and Aim: Surgical site infections (SSIs) in spine surgeries represent one of the most common hospital-acquired infections. SSI (refers to surgical wound infection within 30 days of surgery or 1 year after implant) portends a huge disease burden with devastating consequences for the patient and the hospital facilities with physical and psychological trauma to the patient and it is associated with an increased rate of morbidity and mortality. Despite improvements in the surgical protocol for asepsis and the role of prophylactic antibiotics in clean spine surgeries, a substantial increase still exists in the rate of SSIs. It is essential to review and identify factors predisposing patients with spinal problems to SSIs and its goal is to formulate a local protocol that helps to curtail SSIs and can be replicated in any setting in the world, considering the limitations of our setting. This study aims to review the risk factors for SSI following spine surgeries considering a 54-year-old woman with obesity who had SSI and highlights prevention ways. Methods and Materials/Patients: This study includes the search of the literature using several platforms, such as Google Scholar, Hinari, PubMed, Academia, and other search engines with related keywords to surgical site infections in spine surgery. The retrieved articles were reviewed and in some parts, the narrative case of the 54-year-old obese woman was discussed in the literature. Results: A total of 37 articles were found that matched the search words and satisfied the objective of the study. These articles were reviewed and used in writing this manuscript. Conclusion: SSIs are on the increase, and identifying risk factors on a patient basis is key to prevention. Protocol on preventive measures should be strictly followed to avoid catastrophes associated with SSIs.